GAIT ASSESSMENT IN ANKLE FRACTURES WITH SYNDESMOSIS LESIONS UNDERGOING SURGERY - Romero Montenegro Nery; Giovanni Dela Bianca de Ataide; Rafael Clark Gomes; Dallianny Gonçalves de Sousa Martins; Giovanni Ítalo Gomes de Almeida; Lucas Amaral Shizue Suassuna; Epitácio Leite Rolim-Filho (Acta Ortopédica Brasileira)
ABSTRACT Introduction: The three-dimensional evaluation of patients in the gait laboratory is a diagnostic method that is gaining ground in various orthopedic pathologies and, in the case of ankle fractures, can more accurately detail the degree of joint limitation. Objective: To present the importance of laboratory gait studies in the postoperative period of ankle fractures associated with syndesmosis ligament injuries, increasing the arsenal for assessing whether the surgical approach and outcome were satisfactory. Methods: Case series of 13 patients who underwent surgical treatment for ankle fractures associated with syndesmosis injuries, evaluated postoperatively in the gait clinic using the BTS GAITLAB hardware program. Kinetic and kinematic data using a three-dimensional movement system were collected and analyzed. Results: Alterations were found in the Temporal and Spatial Parameters and in the Statistical Angles of the lower limb joints, comparing the operated limb with the non-operated limb. Conclusion: The results of the study suggest that, despite subtle variations between the limbs assessed, the program was able to identify these differences in a significant way, demonstrating that gait assessments bring great benefits in understanding biomechanical limitations, and make more effective and individualized rehabilitation protocols possible. Level of evidence IV, Case series.